The Influence of Motivation and Work Experience on Employee Performance at PT. Yamaha Saka Motor in South Tangerang - Rozi, Achmad; Sunarsi, Denok (Jurnal Office, 2019)
This study aims to determine the effect of motivation and work experience on employee performance at PT. Yamaha Saka Motor in South Tangerang. The method used was explanatory research with a sample of 43 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study motivation significantly influence employee performance by 47.6%, the hypothesis test obtained significance 0,000 <0.05. Work experience has a significant effect on employee performance by 36.4%, hypothesis testing obtained significance 0,000 <0.05. Motivation and work experience simultaneously have a significant effect on employee performance by 57.6%, hypothesis testing obtained significance of 0,000 <0.05.